Brain contusion with aphasia following an ice hockey injury. Issue 3 (2nd July 2016) - Degen, Ryan M.; Fink, Matthew E.; Callahan, Lisa; Fibel, Kenton H.; Ramsay, Jim; Kelly, Bryan T.
ABSTRACT: Head injuries are relatively common in ice hockey, with the majority represented by concussions, a form of mild traumatic brain injury. More severe head injuries are rare since the implementation of mandatory helmet use in the 1960s. We present a case of a 27 year-old male who sustained a traumatic intraparenchymal hemorrhage with an associated subdural hematoma resulting after being struck by a puck shot at high velocity. The patient presented with expressive aphasia, with no other apparent neurologic deficits. Acutely, he was successfully treated with observation and serial neuroimaging studies ensuring an absence of hematoma expansion. After a stable clinical picture following 24 hours of observation, the patient was discharged and managed with outpatient speech therapy with full resolution of symptoms and return to play 3 months later. We will outline the patient presentation and pertinent points in the management of acute head injuries in athletes.